2016
DOI: 10.1016/j.fsi.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the immune transcriptome in resistant and susceptible hard clams (Mercenaria mercenaria) in response to Quahog Parasite Unknown (QPX) and temperature

Abstract: Quahog Parasite Unknown (QPX) is a fatal protistan parasite that causes severe losses in the hard clam (Mercenaria mercenaria) fisheries along the northeastern coast of the US. Field and laboratory studies of QPX disease have demonstrated a major role for water temperature and M. mercenaria genetic origin in disease development. Infections are more likely to occur at cold temperatures, with clam stocks originating from southern states being more susceptible than clams from northern origin where disease is enzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Temperature has profound effects on the transcriptional activity of organisms, from prokaryotes (Smoot et al, ), plants (Winfield, Lu, Wilson, Coghill, & Edwards, ), fungi (Steen et al, ), invertebrates (Wang, Espinosa, Tanguy., & Allam, ) to vertebrates (Gracey et al, ). In multicellular organisms, temperature‐dependent gene expression responses are often tissue‐specific (Gracey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has profound effects on the transcriptional activity of organisms, from prokaryotes (Smoot et al, ), plants (Winfield, Lu, Wilson, Coghill, & Edwards, ), fungi (Steen et al, ), invertebrates (Wang, Espinosa, Tanguy., & Allam, ) to vertebrates (Gracey et al, ). In multicellular organisms, temperature‐dependent gene expression responses are often tissue‐specific (Gracey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, prior work showed that environmental factors affected host fitness and immune performances leading to enhanced susceptibility or, alternatively, resistance to QPX [ 3 , 4 , 6 , 45 ]. For example, disease prevalence and intensity were markedly higher in clams exposed to low temperatures (13 °C) as compared to animals held at milder temperatures (21 °C and 27 °C) [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Expansion of complement, redox, chaperone, and protein recycling enzyme families across bivalves is thought to have occurred in a species-specific manner ( Wang et al 2010 , 2016 ; Fleury and Huvet 2012 ; Takeuchi et al 2016 ). We found evidence of conserved ancestral duplication (retained by >66% of bivalves) among four gene families (OG92, OG10, OG53, OG314, and OG1538) ( table 1 ).…”
Section: Main Textmentioning
confidence: 99%